ANALISIS DEBIT DAN TINGGI MUKA AIR BANJIR SUNGAI WAY RUHU KOTA AMBON - Laipeny, Teddy Jackson; Warniyati, Warniyati; Sihombing , Tri Octaviani; Tutkey, Monica R. (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
The Way Ruhu River is one of the rivers in Ambon City, Maluku, empties into Ambon Bay, has a length of 8.37 km, and is one of the rivers that is prone to flooding. There have been several floods on this river and the most severe occurred in early August 2012 where flash floods occurred and caused considerable losses to the people living around the Way Ruhu River. The research location was carried out on the Wai Ruhu River in Ambon City - Maluku Province. Geographically, the Wai Ruhu River is located between 3°39'44.18